Analisis Penerapan Perizinan Berusaha Melalui Sistem Online Single Submission (OSS) Berbasis Resiko - Rahmadani, Ardita Esti; Pangestu, Yoga; Halizhah, Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the context of strengthening competitiveness in the national and international areas, the government is holding and seeking to improve licensing. One of them is in terms of business licensing. Where in terms of licensing improvements, the government makes permits on an electronic basis. The research method used in writing this article is to use normative juridical methods. This research is based on laws and regulations, journals, and other documents that are related to the issues discussed. Online Single Submission or OSS can be interpreted as the realization of Law Number 11 of 2020 or the Job Creation Law. In this permit registration stage, we only need to fill in the data and requirements through the OSS system. In this risk-based OSS, the division of business level scale is also seen based on how big the risk level of the business activity is for the environment and society. The distribution of this risk is divided into 4 levels of business risk, namely low, medium low, medium high and high. If seen based on the implementation of the OSS system so far there have been many advances and improvements in the OSS Version of this Risk Based Approach. Progress that can be seen is regarding filling in detailed data in the Risk Based Approach Version of the OSS system so that business actors only really need to register for business licenses through the OSS system. However, the drawback of this risk-based OSS system is regarding guarantees for the protection of personal data that have not been written specifically. Even though there are regulations regarding supervision in this OSS system.